Professor presencial versus professor-tutor: conhecimentos, habilidades e atitudes do profissional na área educacional - Silva, Cátia Regina França de Sousa Gaião e (2011)
Distance Learning (ODL) grew strong in this last decade in function, mainly, of the sprouting of the new technologies of communication mediated by net - necessarily, with the Internet becoming common. The change is not small: new educational methods appear as new conceptions of didactic material, new relationships among human beings and new relations with the knowledgement. However, the relation teacher -pupil is of the utmost importance for the success of the teach-learning process considered excellent determining the good pertaining to school exploitation. To understand the part of the teacher is necessary to know exactly the definition of the parts: the difference and/or complementarity in thedistance education modality and the actual education becomes essential in order to become known a perfect and/or adequate qualification of the professionals of education in the current days. The present study has an objective to verify the competences of the actual teacher and the tutorial teacher are the same ones in the performance in a College of Technology in Management of Human Resources in the distance education modality an actual education in a private university of the city in Rio de Janeiro. In this context, the knowledgement, abilities and attitudes of the actual teacher and the tutorial teacher will be analyzed to investigate the difference of the actual teacher and tutorial teacher acting; if the knowledge, abilities and attitudes are different for the tutorial teacher and the actual teacher and if it has differences in the formal qualification for teaching by the tutorial teacher and/or the actual teacher. Thus, the question problem that motivated the accomplishment of this research is the following one: “Which the competences (knowledge, abilities and attitudes) presented by the professors of a distance Graduation modality”. To implicit form in the question problem proposal is the hypothesis of that has difference in the development of the abilities, competences and attitudes between the tutorial teacher and actual teacher. In the social and educational aspects, this study will be excellent cause pointing the competences, abilities and necessary attitudes to the teacher, one gives credit that the study will contribute for one better performance of the tutorial teacher. For the accomplishment of this research was used map of association of ideas as na analysis of techniques. The citizens that had participated of this inquiry had been actual teachers and tutorial teacher s that works as much in actual education as in distance education in an Institution of Superior Education of the private net in Rio de Janeiro city in the Superior Course of Technology in Management of Human Resources. The instrument of collection of data used in this research was the half-structuralized interview. The analysis method used was qualitative interpreting the data collected by content analysis.